2015
DOI: 10.1007/s00268-015-3183-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Outcome After Surgery for Chronic Groin Pain Following a Lichtenstein Hernia Repair

Abstract: Pain reduction after remedial surgery for chronic groin pain after Lichtenstein repair is more successful if surgery is performed under spinal anaesthesia compared to general anaesthesia. Removal of a meshoma must be considered as success rates are optimized following these measures. Patients using opioids preoperatively have less favourable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
(75 reference statements)
0
14
0
1
Order By: Relevance
“…A new study used QST to distinguish between inflammatory and neuropathic pain and offered a pain operation (mesh removal) to patients with significant inflammatory pain; however, QST was not able to predict the outcome (27). The only study, so far, analyzing preoperative predictors suggested that female gender and opioid use were associated with poorer clinical outcome in 136 patients with chronic pain after Lichtenstein's hernia repair (28).…”
Section: Discussionmentioning
confidence: 99%
“…A new study used QST to distinguish between inflammatory and neuropathic pain and offered a pain operation (mesh removal) to patients with significant inflammatory pain; however, QST was not able to predict the outcome (27). The only study, so far, analyzing preoperative predictors suggested that female gender and opioid use were associated with poorer clinical outcome in 136 patients with chronic pain after Lichtenstein's hernia repair (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies on primary inguinal herniorrhaphy showed that spinal anaesthesia results in shorter hospital stay, less postoperative analgesic requirements, prolonged time to first analgesic requirement, equal operation room time and equal time-to-home readiness [2224]. Only recently, a potential beneficial effect of spinal anaesthesia on surgery for groin pain was demonstrated [15]. This is the first randomised trial comparing two routine anaesthetic modalities for remedial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…All remedial surgeries are performed using an open approach as previously published [15]. Patients are randomised to either spinal or general anaesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations